FORMULASI DAN UJI STABILITAS SEDIAAN MINUMAN ALKALI LIDAH BUAYA (Aloe vera. L) SEBAGAI ANTIOKSIDAN - Marini Marini; Imas Maesaroh; Haty Latifah Priatni (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2022)
Alkaline water is water with a higher pH level than normal drinking water, it has a pH between 7-9.5 and it also has antioxidant activity. Aloe vera (Aloe vera) contains nutrients, vitamins and minerals that can function as natural antioxidants, such as vitamins C, vitamins A, magnesium, and zinc. Fresh aloe vera is less acceptable and preferred because of its taste, so it is necessary to process A. vera into a more durable and acceptable product. This study aims at determining the best and acceptable A. vera alkaline drink formula through product stability testing, including organoleptic, pH measurement, microbiological test. Then, the selected formula is analysed for antioxidant activity using DPPH, while nutritional content testing including fat content, protein content, and carbohydrate content. The result of the stability test of alkaline A. vera drink with concentrations of F1 (10%), F2 (20%), and F3 (30%) after accelerated storage conditions at 5oC and 35oC organoleptically did not change, and ulfilled the requirements under the Minister of Health Regulation of the Food and Drug Administration number 13 of 2019, but the pH decreased because of oxidation reaction of phenolic compounds from A. vera gel which produced aloetic acid and chrysophanic acid. The hedonic test, a result of the selected formula was F3 (30%) had a strong antioxidant activity with an IC50 value of 9.952%, fat content 0.09%, protein content 0.16% and carbohydrate content 57.02%.